Pemanfaatan Tumbuhan Obat Tradisional dalam Upaya Meningkatkan Nafsu Makan Anak Balita - Hanifa Zaini; Mekar Zenni Radhia; Endang Sari; Dewi Asmawati; Nur Hidayah Afnas; Dina Ayuning Tyas; Ira Maulina Sadanoer; Rahmatul Ulya (Institut Nalanda, 2025)
The problem of lack of appetite in toddlers is a challenge that can impact their growth and development. One solution that can be implemented is the use of traditional medicinal plants which have been used for generations to increase appetite. This community service activity aims to provide education to the public regarding types of traditional medicinal plants that are efficacious, proper processing methods, and their safe use. The methods used in this activity include counseling, processing demonstrations, and distribution of guidebooks. The expected result of this activity is increased public understanding of the benefits of traditional medicinal plants and skills in processing them. With proper implementation, it is hoped that there will be an increase in appetite in toddlers resulting in their health and optimal growth.